From Social Interaction to Withdrawal: A Sociological Analysis of the Decline of Male Initiative in Contemporary Romantic Relationships - Iwan Dzulvan Amir; Muba Simanihuruk (Journal of Sumatera Sociological Indicators, 2026)
context of romantic relationships is currently a hot topic of discussion in publicand academic discourse. This article aims to reconstruct and analyzesociologically the changing patterns of gender interaction by placing them in thecontext of the transformation of social norms, power relations, and theinstitutionalization of risk in the modern era. Using a literature reviewmethodology, this article explores various academic sources, media reports, andrelevant analytical essays to understand how changes in culture, law, digitaltechnology, and political economy influence men's rational decision-making inromantic relationships. The results of the study show that the decline in maleinitiative cannot be viewed solely from an individual perspective, such as a lackof confidence, but rather as an adaptive response to social conditions that areconsidered increasingly risky, unbalanced, and uncertain. Social media, datingapps, and the normalization of moral labeling practices contribute to increasedsocial and symbolic costs in gender interactions. This article argues that thisphenomenon reflects structural changes in gender relations, where the logic ofcaution, instrumental rationality, and risk avoidance have become moredominant. These findings have important implications for sociological studies offamily, gender, and culture, particularly in understanding changes in themeaning of intimacy, romance, and the institution of marriage in modernsociety.